Mutational analysis of the cyanobacterial nitrogen regulator PipX. - Karim Boumediene Laichoubi; Javier Espinosa; Miguel Angel Castells; Asunción Contreras (PLoS ONE, 2012)
PipX provides a functional link between the cyanobacterial global transcriptional regulator NtcA and the signal transduction protein P(II), a protein found in all three domains of life as integrators of signals of the nitrogen and carbon balance. PipX, which is toxic in the absence of P(II), can form alternative complexes with NtcA and P(II) and these interactions are respectively stimulated and inhibited by 2-oxoglutarate, providing a mechanism by which P(II) can modulate expression at the NtcA regulon. Structural information on PipX-NtcA complexes suggests that PipX coactivates NtcA controlled genes by stabilizing the active conformation of NtcA bound to 2-oxoglutarate and by possibly helping recruit RNA polymerase. To get insights into PipX functions, we perform here a mutational analysis of pipX informed by the structures of PipX-P(II) and PipX-NtcA complexes and evaluate the impact of point mutations on toxicity and gene expression. Two amino acid substitutions (Y32A and E4A) were of particular interest, since they increased PipX toxicity and activated NtcA dependent genes in vivo at lower 2-oxoglutarate levels than wild type PipX. While both mutations impaired complex formation with P(II), only Y32A had a negative impact on PipX-NtcA interactions.